Electronic devices and circuits - Reddy, S. Rama.; Reddy, Rama S. ([S.l.] : Alpha Science Intl Ltd, 2004)
This new text derived from class tested lecture notes by the author fulfills the needs for a core course in Electrical, Electronics, Instrumentation and Control Engineering. Written in a lucid manner covering the fundamentals of electronic devices and circuits will help the students build a firm foundation on the subject.